Metformin Inhibits Expression and Secretion of PEDF in Adipocyte and Hepatocyte via Promoting AMPK Phosphorylation - Shumin Yang; Qiong Lv; Ting Luo; Lulu Liu; Rufei Gao; Shumei Chen; Peng Ye; Qingfeng Cheng; Qifu Li (Hindawi Limited, 2013)
Objective. Pigment epithelium-derived factor (PEDF) plays an important role in obesity-induced insulin resistance (IR). The study aims to investigate the effect of metformin, a widely used agent to improve IR, on PEDF production both in vivo and in vitro. Methods. SD rats were divided into normal control group, high fat group (HF group), and metformin group (MET group). Hyperinsulinemic euglycemic clamp was performed to evaluate insulin sensitivity. IR models of 3T3-L1 and HepG2 cells were established and then treated with metformin and inhibitor of AMP activated protein kinase (AMPK). Results. In vivo, the HF group showed increased serum PEDF which is negatively correlated with insulin sensitivity, while the MET group revealed decreased serum PEDF and downregulated PEDF expression in fat and liver, concomitant with significantly improved IR. In vitro, the IR cells showed enhanced PEDF secretion and expression, whereas metformin lowered PEDF secretion and expression, accompanied with increased glucose uptake. Metformin stimulated AMPK phosphorylation in fat and liver of the obese rats, while in vitro, when combined with AMPK inhibitor, the effect of metformin on PEDF was abrogated. Conclusions. Metformin inhibits the expression and secretion of PEDF in fat and liver via promoting AMPK phosphorylation, which is closely associated with IR improvement.